Analyzing Business Cycles in G-7 Countries Using Logistic Smooth Transition Autoregressive (LSTAR) Models - Adburaimov, Nodir (Université d'Ottawa | University of Ottawa, 2002)
This paper estimates Logistic Smooth Transition Autoregressive (LSTAR) models to analyze nonlinearities and asymmetries in business cycles using quarterly data GDP for the G-7 countries. The modelling cycle for nonlinear models proposed by Granger and Ter